Millennial Influencer Moral In The Perspective Of Tafsir Maudhu'i - Thohir, Umar Faruq; Lazulfa, Haiyin Lana (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
In this modernist civilization, generations of nations are born with the pleasure of instantiation complemented by various technological advances. Said to be iGeneration, it includes generation-Z which ranges from people born from 1995 to the 2000s. Moral decadence occurs without being felt, this becomes an inequality in itself for the nation. This has been mentioned in several verses in the Qur'an, among them al-Ahzab [33]: 21, al-Baqarah [2]: 83 and 152, an-Nahl [16]: 90. These verses broadly discuss morals. Through this verse will be found about the morality of the Qur'an that should exist in the next generation of this nation. Through a thematic approach, this research will be carried out in-depth to find the Qur'anic view on the morality of Millennial Influencers. This research was conducted by dissecting verses related to morals, which were then linked to morals. Then it is interpreted as tahlili and ijmali and compares it with related interpretations. Through the search for this thematic interpretation, based on Q.S an-Nahl [16]: 90 it can be understood that morality is very important for life which will determine the direction of good and bad, right wrong, appropriate, and not one's behavior